FLM-based AFL improves physics engagement and conceptual understanding - Asyhari, Ardian; Irawan, Windo Dicky; Sunyono, Sunyono; Rosidin, Undang; Sowiyah, Sowiyah; Hariri, Hasan (Intelektual Pustaka Media Utama, 2024)
Assessment for learning (AFL) is a pedagogical approach that enhances student learning outcomes through high-quality feedback. This study investigates the effectiveness of integrating the feedback loop model (FLM) with AFL to improve students' engagement and understanding of physics, specifically in kinematics and motion dynamics. The study employs a mixed-methods research design, combining quantitative and qualitative data to assess the impact of the FLM-based AFL approach. A one-group pretest-posttest design was used, supported by research instruments that measured student engagement and their conceptual grasp of physics. The findings indicate that integrating FLM into AFL led to significant improvements, evidenced by Cohen’s effect size of 1.91, highlighting a substantial impact on student learning. These results affirm that FLM-based AFL positively affects student engagement and understanding of physics. The study contributes to the existing research on effective assessment methods, providing valuable insights for educators and policymakers in developing enhanced assessment and teaching strategies. This study emphasizes the potential benefits of incorporating FLM-based AFL in diverse educational settings to elevate student learning experiences and outcomes.